Editorial: infliximab trough cut‐off for perianal Crohn's disease – another piece of the therapeutic drug monitoring‐guided infliximab dosing puzzle. Issue 9 (3rd April 2017) - Mitrev, N.; Kariyawasam, V.; Leong, R. W.
Abstract : Linked Content This article is linked to Yarur et al paper. To view this article visithttps://doi.org/10.1111/apt.13970 .